Physio-Chemical and Microbial Quality of Kurdish Soft Cheese from Sulaimani Market - Zardasht Ali, Zardasht (University of Thi-Qar Journal of agricultural research, 2025)
This study looked into the quality of Kurdish soft cheese sold in local markets across Sulaimani city, Iraq. Between February and May 2024, fifteen cheese samples were collected and thoroughly analyzed. The results showed quite a bit of variation among the samples. Moisture content ranged from 46.3% to 64.9%, protein from 19.5% to 26.8%, fat from 13.2% to 23.5%, and salt from 1.6% to 3.7%. pH values were between 6.19 and 6.73, while acidity ranged from 0.95% to 2.29% as lactic acid. The hardness of the cheese varied widely, from 162.5 g up to 452.5 g. On the microbiological side, TVC ranged from 4.0 × 10³ to 1.2 × 10⁷ CFU/g. Coliforms were found in 80% of the samples, with counts between 2.4 × 10² and 5.2 × 10² CFU/g, and yeast and mold counts went as high as 6.7 × 10³ CFU/g. Overall, these findings highlight significant inconsistencies in the quality of Kurdish soft cheese sold in Sulaimani. They also point to shortcomings in hygiene practices during production and handling. This underscores the need for better quality control and stricter manufacturing standards to protect consumer health.